Non-invasive evaluation of hydrogen peroxide concentrations in a drinking bottle by near-infrared spectrometry - Bashirun Che Morat, 1977-; Herlina Abdul Rahim, supervisor; Fakulti Kejuruteraan Elektrik (2012)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2012